Detection and Isolation of Malicious Nodes for Selective Forwarding Attack in Wireless Sensor Network - Reenu, Reenu; Singh, Amarvir (International Journal of Computer Sciences and Engineering, 2025)
A wireless sensor network includes incalculable number of nodes spread over a specific region, where we have to deal with the movements proceeding there. A sensor center, generally, contains sensors, actuators, memory, a processor and they do have correspondence limit. These sorts of networks are much feeble against security attacks. Numerous sorts of dynamic and detached attacks are possible in the sensor network. Among all the possible dynamic attacks, selective forwarding attack is the most generally perceived and ruinous attack. This attack degrades network execution and prompts denial of service attack. The malicious hub activates the attack, which is accessible in the network. In this work, a novel technique has been proposed to perceive and withdraw malicious nodes from the network, which is responsible for triggering the attack. The proposed technique depends on the threshold technique for recognition of malicious nodes. The exploratory outcomes will exhibit that proposed methodology distinguishes and separate the malicious nodes from the network capably. It will upgrade network adequacy to the extent package adversity, concede and grow throughput of the network. NS2 simulator instrument will be used as a piece of it